Synthesis, in silico and in vitro antimicrobial efficacy of substituted arylidene-based quinazolin-4(3H)-one motifs - Oduselu, Gbolahan O.; Aderohunmu, Damilola V.; Ajani, Olayinka O.; Elebiju, Oluwadunni F.; Ogunnupebi, Temitope A.; Adebiyi, Ezekiel (Frontiers in Chemistry, 2023)
Quinazolin-4(3H)-one derivatives are of considerable attention in pharmacological profiling of therapeutic drug targets. Thus, this present study unveils the development of arylidene-based quinazolin-4(3H)-one motifs as potential antimicrobial drug candidates. The synthetic pathway was initiated through thermal cyclization of acetic anhydride on anthranilic acid to produce 2-methyl-4H-3,1-benzoxazan-4-one 1 which upon condensation with hydrazine hydrate gave 3-amino-2-methylquinazolin-4(3H)-one 2. The reaction of intermediate 2 at its amino side arm with various benzaldehyde derivatives furnished the final products as substituted benzylidene-based quinazolin-4(3H)-one motifs 3a-l and with thiophene-2-carbaldehyde to afford 3m. The purified targeted products 3a-m were effectively characterized for structural authentication using physicochemical parameters, microanalytical data and spectroscopic means including IR, UV, 1H- and 13C-NMR as well as mass spectral data. The substituted arylidene-based quinazolin-4(3H)-one motifs 3a-m were screened for both in silico and in vitro antimicrobial properties against selected bacteria and fungi. The in silico studies were carried out using predicted ADMET screening, molecular docking and molecular dynamics (MD) simulation studies. Furthermore, the in vitro experimental validations were performed using agar diffusion method and the standard antibacterial and antifungal drug used were gentamicin and ketoconazole respectively. Most of the compounds possessed good binding affinities from the molecular docking studies while the MD simulation revealed their structural stabilities in the protein-ligand complexes. 2-methyl-3-((thiophen-2-ylmethylene)amino)quinazolin-4(3H)-one 3m emerged as both the most active antibacterial agent (MIC value of 1.95 μg/mL) against S. aureus and antifungal agent (MIC value of 3.90 μg/mL) against C. albicans, A. niger and R. nigricans.